주파수 선택성 레일라이 페이딩 환경에서 STBC-OFDM 시스템의 성능 비교 분석 - 이상호; Sang Ho Lee; 정호철; Ho Chul Jung; 박형래; Hyung Rae Park; 김종호; Jong Ho Kim (한국항행학회논문지, 2004)
In this paper we apply the space-time block codes (STBCs), the key technologies for the 4th generation mobile communication systems, to the OFDM system and analyze their performances. First, we derive the signal models for representative STBC schemes and demodulation procedures for each scheme. We also select the parameters for OFDM system considering mobile cellular environments and assign adequate modulation schemes to STBC-OFDM schemes according to the transmission rate from 2bps/Hz to 4bps/Hz. We finally compare and analyze the performances of STBC-OFDM schemes for the selected transmission rates through computer simulations, together with performance comparison when the same modulation scheme being adopted. 본 논문에서는 4세대 이동통신시스템의 핵심 기술인 Space-Time Block Code (STBC)를 OFDM 시스템에 적용하고 주파수 선택적 레일라이 페이딩 환경에서 각 방식의 성능을 시뮬레이션을 통해서 비교, 분석한다. 먼저 주요 STBC 방식들의 신호 모델과 각 방식별로 복조과정을 유도한다. 또한, 이동통신 환경을 고려하여 OFDM 시스템 파라메타를 설정하고 2bps/Hz에서 4bps/Hz 까지의 전송율에 대해 STBC 방식별로 적절한 변조방식을 설정하여 각각의 전송속도에 대해 STBC-OFDM 방식들의 성능을 컴퓨터 시뮬레이션을 통해 비교, 분석한다. 이 밖에, 각 STBC-OFDM 방식들이 동일한 변조방식을 사용할 경우에 대해서도 성능을 비교, 분석한다.